2021
DOI: 10.3906/sag-2006-103
|View full text |Cite
|
Sign up to set email alerts
|

20-year experience on prenatal diagnosis in a reference university medical genetics center in Turkey

Abstract: Background/aim: Although cutting edge procedures such as cell-free fetal DNA isolation from maternal blood are now available, invasive prenatal tests are still being used extensively for prenatal diagnosis. The study aims to evaluate the demographic data, indications, and cytogenetic results of 9297 results of patients who underwent prenatal invasive testing for genetic analysis that were referred for the last 20 years in a University Medical Genetics Center. Materials and methods: The records of 8363 amniocen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 19 publications
(27 reference statements)
0
2
0
Order By: Relevance
“…In a recent study from Turkey about the experiences of mothers with DS, it was determined that approximately 81.4% of families did not know about this condition before birth (Buyukavci et al, 2019). In a recent study, when DS risk increase was examined according to age groups after the age of 35, it was reported that the risk increase was 2 times in the 36-40 age group, 5 times in the 41-45 age group and 10 times in the 46-54 age group (Durmaz et al, 2021). In the same study, it was emphasized that advanced aged pregnancies increase the risk and advanced maternal age is still the most common risk for indication of genetic diagnosis for DS in the relevant center in Turkey.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a recent study from Turkey about the experiences of mothers with DS, it was determined that approximately 81.4% of families did not know about this condition before birth (Buyukavci et al, 2019). In a recent study, when DS risk increase was examined according to age groups after the age of 35, it was reported that the risk increase was 2 times in the 36-40 age group, 5 times in the 41-45 age group and 10 times in the 46-54 age group (Durmaz et al, 2021). In the same study, it was emphasized that advanced aged pregnancies increase the risk and advanced maternal age is still the most common risk for indication of genetic diagnosis for DS in the relevant center in Turkey.…”
Section: Discussionmentioning
confidence: 99%
“…, 2019). In a recent study, when DS risk increase was examined according to age groups after the age of 35, it was reported that the risk increase was 2 times in the 36–40 age group, 5 times in the 41–45 age group and 10 times in the 46–54 age group (Durmaz et al. , 2021).…”
Section: Discussionmentioning
confidence: 99%